AN ASSESSMENT OF PRE-PRIMARY SCHOOL PROGRAMME ACTIVITIES IN KWARA STATE, NIGERIA - Muhinat, Bello; Ijeoma, Okafor; I. O.O., Amali (European Scientific Journal, ESJ, 2012)
In the current National Policy on Education (NPE, 2004) Pre-primary education or early childhood education has taken a centre stage as a process of educating young children in educational institutions prior to their entry into primary schools. This study thus assesses Preprimary schools programme activities across Kwara State, Nigeria. The objective is to determine the extent to which the programme on the ground has met with the stipulated policy statement as contained in the National Policy on Education. The study used a descriptive survey design and used researchers’ design questionnaire (design along likert-type) to collect its data. Using a simple random technique, the study sampled responses from 265 teachers (males and females) drawn from the three senatorial districts of Kwara State, Nigeria. It answered four (4) research questions. The findings revealed the jeopardy due to: the lack of government adherence to the objectives of the policy in respect of adequate funding, infrastructural development, material and non – material resources and standard curriculum guidelines as stipulated in the policy statement. It thus recommended that the Federal, State and Local governments should be more committed and proactive to contribute positively to the implementation and enforcement of the policy in Kwara State, Nigeria. The findings in this study would thus serve as a yardstick for success or otherwise of the policy statement as contained in the National Policy on Pre-primary education which would serve in facilitating actions toward improving Pre-primary education in Kwara State and in Nigeria in general.